Imaging and spectroscopy of domains of the cellular membrane by photothermal-induced resonance. Issue 17 (24th July 2020) - Quaroni, Luca
Abstract : Photothermal induced resonance measurements allow imaging and spectroscopy of the cellular surface with membrane selectivity. Abstract : We use photothermal induced resonance (PTIR) imaging and spectroscopy, in resonant and non-resonant mode, to study the cytoplasmic membrane and surface of intact cells. Non-resonant PTIR images apparently provide rich details of the cell surface. However, we show that non-resonant image contrast does not arise from the infrared absorption of surface molecules and is instead dominated by the mechanics of tip–sample contact. In contrast, spectra and images of the cellular surface can be selectively obtained by tuning the pulsing structure of the laser to restrict thermal wave penetration to the surface layer. Resonant PTIR images reveal surface structures and domains that range in size from about 20 nm to 1 μm and are associated with the cytoplasmic membrane and its proximity. Resonant PTIR spectra of the cell surface are qualitatively comparable to far-field IR spectra and provide the first selective measurement of the IR absorption spectrum of the cellular membrane of an intact cell. In resonant PTIR images, signal intensity, and therefore contrast, can be ascribed to a variety of factors, including mechanical, thermodynamic and spectroscopic properties of the cellular surface. While PTIR images are difficult to interpret in terms of spectroscopic absorption, they are easy to collect and provide unique contrast mechanisms without any exogenous labelling. As such they provide a new paradigm in cellular imaging and membrane biology and can be used to address a range of critical questions, from the nature of membrane lipid domains to the mechanism of pathogen infection of a host cell.